O processo argumentativo como elemento problematizador na produção de materiais didáticos por licenciandos - Reis, Alícia Rodrigues dos (2023)
Bearing in mind how challenging scientifically literate students can be, this research project presents discussions about the insertion of didactic practices that could help in the development and elaboration of arguments through the construction of didactic materials, seeking to weave relationships with the importance that the teacher training may be linked to their immersion in a more premature way in the school environment. The production of these materials was carried out by a group of teachers in training, members of the Pedagogical Support Program Graduates at School - PROLICE - Nucleus of Chemistry - UFS, analyzing which activities and how they were inserted taking into account the favoring of space for the argumentation was generated, in addition to finding out how the use of these approaches were inserted, emphasizing the process of reflection on such strategies. Considering this context, this is a qualitative research, which aims to investigate how the process of argumentation is considered in the elaboration of didactic materials with investigative activities with a group of undergraduate students of the Chemistry course inserted in a Program of Initiation to Teaching at UFS. The study was methodologically structured through the development of investigative activities to promote argumentative development, adopting Design Research, also known as development research through a training course mediated by the researcher in question, seeking to weave relationships between what they considered important for the elaboration of this material through the discussion of texts, articles and their experiences in general, in addition to what would be introduced with the objective of assisting in the argumentative development and how this insertion would take place. The audio recordings of these meetings were transcribed, coded and interpreted according to the Content Analysis technique by Moraes (1999), also analyzing which moments were modified and/or inserted, comparing them with the first version of the material presented by them. Among the results achieved, it was observed that the undergraduates considered important the insertion of experimental investigative activities, the promotion of interactions and discussions among students, as well as considering the context during the elaboration of these activities, in addition to emphasizing that the elaboration of a strategy of teaching through the production of didactic material linked to its development and construction can help in the argumentative process of students and in teacher training, leading them to reflect on the relevance of theoretical knowledge during the construction of a teaching method.